In vitro modeling of glucocorticoid mechanisms in stress-related mental disorders: Current challenges and future perspectives - Bassil, Katherine; De Nijs, Laurence; Rutten, Bart P. F.; Van Den Hove, Daniel L. A.; Kenis, Gunter (Frontiers in Cell and Developmental Biology, 2022)
In the last decade, in vitro models has been attracting a great deal of attention for the investigation of a number of mechanisms underlying neurological and mental disorders, including stress-related disorders, for which human brain material has rarely been available. Neuronal cultures have been extensively used to investigate the neurobiological effects of stress hormones, in particular glucocorticoids. Despite great advancements in this area, several challenges and limitations of studies attempting to model and investigate stress-related mechanisms in vitro exist. Such experiments often come along with non-standardized definitions stress paradigms in vitro, variations in cell models and cell types investigated, protocols with differing glucocorticoid concentrations and exposure times, and variability in the assessment of glucocorticoid-induced phenotypes, among others. Hence, drawing consensus conclusions from in-vitro stress studies is challenging. Addressing these limitations and aligning methodological aspects will be the first step towards an improved and standardized way of conducting in vitro studies into stress-related disorders, and is indispensable to reach the full potential of in vitro neuronal models. Here, we consider the most important challenges that need to be overcome and provide initial guidelines to achieve improved use of in vitro neuronal models for investigating mechanisms underlying the development of stress-related mental disorders.